Influence of allograft weight to recipient bodyweight ratio on outcome of cadaveric renal transplantation. Issue 7 (16th June 2014) - Codas, Ricardo; Danjou, Fabrice; Dagot, Celine; Martin, Xavier; Morelon, Emmanuel; Badet, Lionel; Hanf, William; Petruzzo, Palmina
Abstract Aim One of the factors that may affect survival and function of kidney graft is its functional mass. Methods In a prospective study, we investigated the impact of the ratio between donor kidney weight in grams and recipient bodyweight in kilograms (DKW/RBW) on creatinine clearance, inulin clearance, and proteinuria: 154 kidneys from deceased donors were weighed and the mean kidney weight was 227 ± 59 g, the bodyweight of the recipients was 64 ± 19 kg. Results This study showed significant lower values of modification of diet in renal disease (MDRD) in patients with DKW/RBW ratio 2.5 g/kg and between 2.5 and 4.5 g/kg compared with those with DKW/RBW ratio >4.5 g/kg as well as in patients with DKW/RBW ratio <3 g/kg and between 3 and 4 g/kg compared with those with DKW/RBW ratio >4 g/kg; moreover a random coefficient model showed a different time evolution in creatinine clearance values in patients with DKW/RBW ≤ 3 g/kg when compared with patients with DKW/RBW ratio >4 g/kg. There were significant lower values of inulin clearance in patients with DKW/RBW ratio between 2.5 and 4.5 g/kg compared with those with DKW/RBW ratio >4.5 g/kg at 12 post‐transplant months and a significantly greater occurrence and earlier appearance of proteinuria in the recipients with DKW/RBW ratio <2.5 g/kg. DKW/RBW ratio did not influence DGF incidence and graft survival. Donor and recipient gender, number of acute rejection episodes and donor age also significantly influenced MDRD values. Conclusions Measurements of graft weight as well as donor kidney and recipient body matching should be recommended as influencing renal function.